PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MENGGUNAKAN MODEL PEMBELAJARAN LANGSUNG KELAS V SEKOLAH DASAR - Purwanti, Wiwit (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The general objective of this research is to improve the writing skills of narrative essay using direct learning model in class V. This research uses descriptive method with a form of action research, and the nature of research is collaborative. This research took place at school 03 Pontianak City with research subjects are students of class VA totaling 38 student.Technique collecting data that used are observations with data collection tool observation sheets and technical documents learning outcomes by means of collecting data document learning outcomes. The data were analyzed by calculating the average and percentage. This research was conducted as the second cycle. The results obtained are the ability of teachers to design learning first cycle with an average score of 3.12, the second cycle increased by an average score of 3.95. The results of the research ability of teachers to implement learning cycle I with an average score of 3.29, the second cycle with an average score of 3.98. Student learning outcomes in learning writing a narrative essay first cycle the average is 75.91, and the second cycle averaged 83.64. From the analysis of the data obtained, this shows that the use of direct learning model can improve writing skills of narrative essay. Keywords: writing skills, narrative essay, direct instruction